مقاييس الرقابة و الأمان للبيانات المحاسبية في ظل نظام المعلومات المححوسب : دراسة ميدانية على البنوك التجارية في الاردن - د.عبدالناصر نور; د.نائل عدس (PROSPECTIVE RESEARCHES, 2023)
The present study is an attempt to show the control limit on the financial data and the safety description of information technology system. The study aims to point out the weak points of information technology systems. It also presents some suggestions to mend and test the internal control systems on those systems to discover the weak points and the fraud and misacting operations as well as data hacking to be able to get accurate and safe output information. The study consists of the theoretical part which has been based on recent resources and the practical one which has been based on a questionnaire distributed to banks in which such systems are used most.